421 Prevalence of cachexia in treatment-naïve patients with gynaecological cancer: a systematic review. (13th November 2020) - O'Donoghue, N; O'Connor, B; Thompson, C; Gleeson, N
Abstract : Background: Approximately half of all cancer patients develop cachexia, with 20% of cancer-related deaths attributed to cachexia. Gynaecological cancer has not featured extensively in published cachexia literature. Prevalence of cachexia in this population is therefore unclear. The aim of this review is to report estimated prevalence of cachexia in patients with gynaecological cancer prior to treatment. Methods: A systematic review was conducted to estimate the prevalence of cachexia at diagnosis in patients with gynaecological cancer. CINAHL, Cochrane Library, EMBASE, MEDLINE Ovid, Scopus and Web of Science were searched and additional relevant articles were identified by hand searching a number of key journals. A narrative synthesis was used to integrate the findings from the included studies. Results: Following de-duplication, the title and abstracts of 7894 articles were screened; two studies were identified as eligible for inclusion. Both included patients with a cervical cancer diagnosis. Prevalence of cachexia ranged from 0 – 32.4%. Conclusions: Well-designed and robust studies in treatment-naive patients with gynaecological cancer are needed in order to quantify the true prevalence of cachexia. This would support the early identification of at-risk patients for whom interventions may be most beneficial.